Role of Self-Assessment in Improving Students' Writing: A Systematic Review - Ghazala Eswaey,; Hayah Ihmoumah, (AlQalam Journal of Medical and Applied Sciences, 2024)
The process of writing is highly significant in the field of education as a means of communication. Writing proficiency is an important skill that EFL students are required to achieve during their academic careers. However, developing academic writing skills can be difficult for students as well as teachers. Various instructional strategies and interventions have been investigated to improve the quality of students' writing. Self-assessment is one such method that has received a great deal of attention. With the growing emphasis on self-assessment in students’ writing development, the review aims to provide an updated comprehensive synthesis of the current literature on self-assessment and its relationship with writing skills. The current review seeks to identify, describe, and synthesize the most rigorously available recent evidence base on the role self-assessment plays to improve EFL students’ writing skills. About 30 papers from 2010 to 2023 that were relevant to the topic of this paper were selected for the review process. Findings of this review indicate that self-assessment can play a role in improving the learning experience of students in general through improving their self-awareness and satisfaction; let alone improving writing skills. That is, the more students employ self-assessment and are aware of their mistakes, the better their writing skills are. Overall, learning writing skills is as teaching it, always challenging. Some recommendations for EFL teachers and implications for policy are discussed. إن عملية الكتابة لها أهمية كبيرة في مجال التعليم كوسيلة للتواصل. ويعد إتقان الكتابة مهارة مهمة يتعين على طلاب اللغة الإنجليزية كلغة أجنبية تحقيقها خلال حياتهم المهنية الأكاديمية. مع ذلك، قد يكون تطوير مهارات الكتابة الأكاديمية أمرًا صعبًا بالنسبة للطلاب والمعلمين على حدٍ سواء. تم دراسة الاستراتيجيات والتدخلات التعليمية المختلفة لتحسين جودة كتابة الطلاب وكان التقييم الذاتي هو أحد هذه الأساليب التي حظيت بقدر كبير من الاهتمام. ومع التركيز المتزايد على التقييم الذاتي في تطوير الكتابة لدى الطلاب، تهدف المراجعة إلى تقديم توليفة شاملة محدثة للأدبيات الحالية حول التقييم الذاتي وعلاقته بمهارات الكتابة. حيث تسعى المراجعة الحالية إلى تحديد ووصف وتجميع قاعدة للأدلة الحديثة المتوفرة حول الدور الذي يلعبه التقييم الذاتي لتحسين مهارات الكتابة لدى طلاب اللغة الإنجليزية كلغة أجنبية. تم اختيار حوالي 30 ورقة بحثية من عام 2010 إلى عام 2023 كانت ذات صلة بموضوع هذه المراجعة الاستعراضية. تشير نتائج هذه المراجعة إلى أن التقييم الذاتي يمكن أن يلعب دورًا في تحسين تجربة التعلم لدى الطلاب بشكل عام من خلال تحسين الوعي الذاتي والرضا لديهم؛ ناهيك عن تحسين مهارات الكتابة. أي أنه كلما زاد عدد الطلاب الذين يستخدمون التقييم الذاتي وأصبحوا على دراية بأخطائهم، كانت مهاراتهم في الكتابة أفضل. بشكل عام، تعلم مهارات الكتابة مثل تعليمها، يُمثّل تحديًا دائمًا. أخيراً، ستتم مناقشة بعض التوصيات لمعلمي اللغة الإنجليزية كلغة أجنبية والآثار المترتبة على السياسات المتبعة